Effectiveness of The Inquiry Training Model to Improve Students' Critical Thinking Skills in Learning: Systematic Literature Reviews and Meta-Analysis - Wiwid Suryono; Linda Winiasri; Tomi Apra Santosa; Baso Intang Sappaile; Moh. Solehuddin (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of the Inquiry training model to improve students' critical thinking skills in science learning. This type of research is a systematic literature review and meta-analysis.Â Research data sources come from national and international journals. The process of searching for sources in this study through the google scholar database, Eric, ScienceDirect, Wiley, Taylor or Francis, and ProQuest. Data collection techniques with direct observation and documentation. Inclusion criteria in this study are journals or proceedings indexed by SINTA, DOAJ, EBSCO, and Scopus; type of experimental or quasi-experimental research; research variables related to inquiry training in science learning (Biology, physics, and chemistry); journal or proceedings published in 2017-2023 and 5) Has complete research data standard deviation, Standard Erro, t value, and others. The data analysis technique is quantitative statistical data analysis with the help of the JSAP application. The results showed an average effect size value of (ES = 1.90) and a Standard Error (SE = 0.67). The results of these findings indicate that the inquiry training model effectively increases students' critical thinking skills in science learning